PROPOXUR SELECTION OF THE ADULTS OF ANOPHELES STEPHENSI FROM MINAB, SOUTH OF IRAN - H. Edalat; M.R. Yaghoobi Ershadi (Tehran University of Medical Sciences, 1997)
Anopheles stephensi is the main malaria vector in south of Iran. It has been known to be resistant to DDT, malathion and dieldrin. After appearance of resistance the area was treated with propoxur, at the rate of 2 g/m2 twice a year for 14 successive years. This species is still susceptible to propoxur. In order to forecast the possibility of development of propoxur resistance in An.stephensi, the females of this species were put under the pressure of propoxur for 14 generations in 1988. Fourteen generations of propoxur selection on the adult females of An.stephensi resulted in an increase in LT60 from 8.5 min to 24.30 minutes, i.e. 2.86 fold increase in tolerance.